Development and Evaluation of Improved Saddle of Yak for Enhancement of Pack-load Capacity on Steep Slopes in Hills -A Case Study in NER - Tiwari, R. K.; Chauhan, S. K.; Din, M.; Rautaray, S. K.; Chaudhuri, D. (Indian Journal of Hill Farming, 2018)
The Yak rearing states of India are Arunachal Pradesh, Sikkim, Himachal Pradesh and Jammu and Kashmir. The total number of Yaks were 65000 (Indian Livestock Census 2003) in India including 7000 in Sikkim. There were number of phenotypic types amongIndian Yak. The common Yak resembled medium size hill cattle in conformation. Bisonian Yak were found as bigger animals having bare back, long body and little hair on their backs. Among the ten colour patterns available in India, the majority were black(29%) and black with white patches (40%). Some are of brown with white patches. Yak in Sikkim are generally used as pack animals for transport of goods and for riding and trekking. Yak is an important animal in high hills and snow bound areas due to their unique ability to survive in extreme cold climates. Yak is the main-stay for the highlander’s dwellings in mid and higher reaches of Sikkim providing transport. In Arunachal Pradesh (District: West Kamrang, location Derang hills), the local yak (weight :350 kg) using traditional saddle (weight : 4.7 kg) showed pack load capacity of 80 kg negotiating 60% slope for travelling 3 km in one hour duration. The respiration rate, pluse rate of yak (weight: 350 kg, age: 3 years) increased 17% and 26% respectively for covering one km distance slope negotiating 60%. The test trial of developed improved saddle (weight: 3.2 kg) made using composite material was conducted at Thangu region (Altitudes 4270 - 4800 m) in north Sikkim district. The maximum pack load of 120 kg (three bags of potato each of 40 kg weight) on yak could be transported covering 5.5 km distance (travel speed : 2.62 km/h) in two hour duration at steep up slope of 60 degree. Itshowed that newly developed saddle was able to take 30% more load over traditional saddle. The physiological responses (respiration rate/min, pulse rate/min and body temperature in 0C) were measured before and after the test trial. The result showed that respiration rate, pulse rate and body temperature were increased by 22%, 31% and 1.7% during two hours trial. The improved design of saddle provided higher work output besidescomfort to the animals. Replacement of saddle materials was considered keeping in view the cost-effectiveness, light weight, cushioning effect with lower body surface friction andeasy availability and affordability.